Physical exercise as a tool for the treatment of eating disorders - Sofía Mª Martínez Sánchez; Diego Munguía-Izquierdo (INFAD, 2017)
Eating disorders (ED) include those pathologies in which the obsession with thinness and the fear of obesity condition the appearance of an inadequate eating pattern and pathological behaviors linked to weight control. Exercise has historically been considered as one of the symptoms in this disease, and therefore it has been excluded as treatment in these patients. Within the ED, we can observe a problematic behavior to the exercise (compulsive exercise) and not necessarily it occurs in all the patients that suffer this pathology. There is evidence that participation in structured and supervised exercise programs (high-intensity resistance training or yoga) can be very useful in this clinical population, since it reduces psychopathology, it improves muscular strength, quality of life, psychological well-being and it facilitates compliance and adherence to treatment.